The role of irisin in ischemic heart disease - Piątek, Patrycja Agata; Fabian-Danielewska, Anna; Korabiusz, Katarzyna; Stecko, Monika; Wawryków, Agata; Witkiewicz, Wojciech; Stachowiak, Paweł; Gorący, Jarosław (Journal of Education, Health and Sport, 2019)
Introduction: Physical effort has a positive effect on the human body, through its protective effect on the development of many diseases, along with cardiovascular system diseases. Irisin is an adipomiokine that is a fragment of the doemeny of extracellular FNDC5 protein. It is released from FNDC5 due to physical activity and peroxisome proliferator receptor-γ coactivator 1α (PGC-1α) stimulation. It forms a link between the muscles and other tissues of the body. Moreover, it affects the conversion of white adipose tissue into brownish-like fat tissue. Aim: For over 15 years ischemic heart disease has been one of the most common causes of death in the world. Therefore, attempts have been made to clarify the role it has in ischemic heart disease. Conclusions: It has been proven, that the concentration of irisin decreases in patients with myocardial infarction it also correlates with the severity of stable coronary disease and a higher SYNTAX score. Hence, the hypothesis was that the level of this protein probably depends on the inflow of blood to the myocardium. It can therefore be used for the panel of myocardial damage. The New Approach of therapeutic options uses irisin with stem cells during the repairing of myocardium. Despite much interest in irisin, there are still many questions that need to be answered, in particular those related to the irisin cell receptor and what is related to the clarification of its mechanisms in physiology.